Late Pleistocene Clovis atlatl hunting fails a chronological modeling test - Metin I. Eren; Michelle R. Bebber; Robert S. Walker; C. Reagan Johnson; Briggs Buchanan (Proceedings of the National Academy of Sciences, 2026)
Late Pleistocene North American foragers assigned to the Clovis culture have long been assumed to have hunted megafauna with the atlatl, which would have provided several advantages. Yet, we chronologically modeled radiocarbon ages from preserved Holocene atlatls and show that Clovis atlatl use is not supported. If Clovis hunters did not use atlatl technology, then its emergence in the Americas during the early Holocene represents a case of technological convergent evolution analogous to atlatls in Late Pleistocene Europe. A further implication is if Clovis hunters used spears, javelins, or bow technology then models concerning megafaunal hunting need to be rethought given the distinct effectiveness, hunting risk, and tactics associated with these weapons.